2008
DOI: 10.1007/s10585-008-9231-x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin utilizes Jun N-terminal kinases to stimulate the invasion of MCF-7 breast cancer cells

Abstract: In breast tumors, high levels of leptin have been associated with increased incidence of breast cancer metastasis. Breast cancer metastasis is directly associated with breast cancer cell invasion. However, whether leptin could augment breast cancer cell invasion is not known. Here we showed that leptin increased the invasiveness and the matrix metallo-proteinase-2 (MMP-2) activity of the MCF-7 breast cancer cell line. Leptin stimulated the phosphorylation of extracellular signals regulated kinases, signal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…Castellucci et al (2000) reported that leptin dose-dependently enhances secretion of MMP-2 and the activity of MMP-9 in cultured cytotrophoblastic cells. Consistent with this finding, McMurtry et al (2009) demonstrated that activated Janus-activated kinase 2 (JNK) led to enhanced MMP-2 activity, and ultimately caused an increase of MCF-7 human breast cancer cell invasion.…”
Section: Leptin and Tumor Invasionsupporting
confidence: 53%
“…Castellucci et al (2000) reported that leptin dose-dependently enhances secretion of MMP-2 and the activity of MMP-9 in cultured cytotrophoblastic cells. Consistent with this finding, McMurtry et al (2009) demonstrated that activated Janus-activated kinase 2 (JNK) led to enhanced MMP-2 activity, and ultimately caused an increase of MCF-7 human breast cancer cell invasion.…”
Section: Leptin and Tumor Invasionsupporting
confidence: 53%
“…The invasiveness of MCF-7 and MCF-7/ PDCD4 cells treated with leptin was determined as previously described (14,19) by counting the number of cells that invaded through transwell inserts coated with the Matrigel artificial basement membrane. Briefly, MCF-7 and MCF-7/PDCD4 cells were collected and washed with serum-free media.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described (14). Cells were harvested with cold PBS, and lysed with ice-cold lysis buffer and incubated on ice for 30 min.…”
Section: Rna Isolation and Reverse Transcription-polymerase Chain Reamentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies demonstrate that leptin stimulates breast cancer cell growth and survival. The hormone can also increase the invasiveness and metastatic potential of BC cells [15], and promote angiogenesis while maintaining a microenvironment favorable for BC development [16]. Furthermore, leptin is known to crosstalk with and transactivate several pathways that are targets for BC therapy, including the estrogen, EGF receptor and HER2 pathways [13,17,18].…”
Section: Themed Article Y Breast Cancermentioning
confidence: 99%